Countering violent extremism in Pakistan: local actions, local voices - Weiss, Anita M. (Oxford University Press, 2020)
This book identifies and analyzes the impact of the various ways in which local people are responding, taking stands, recapturing their culture, and saying 'stop' to the violent extremism that has manifested over the past decade (even longer) in Pakistan. Local groups throughout Pakistan are engaging in various kinds of social negotiations and actions to lessen the violence that has plagued the country since the 1979 Soviet invasion of Afghanistan which let loose a barrage of violence that overflowed into its borders. In so many ways, Pakistanis are engaging in powerful actions that transform how people think about their own society, impeding extremists' rants while acting on 'envisioning alternative futures'